First record of cannibalism in the red-finger rubble crab Eriphia gonagra (Fabricius, 1781) (Decapoda, Eriphidae) in a natural environment - Camylle Santos Matos; Alyne Dias da Silva; Noumie Alves Machado; Pablo Augusto Gulhões da Silva; Pedro Lucas Souza de Andrade; Carlos Eduardo Rocha Duarte Alencar (Discover Animals, 2025)
Abstract Cannibalism is considered a natural intraspecific interaction, being a response of organisms to available food resources, or in other cases, associated with high levels of environmental stress. The red-finger rubble crab Eriphia gonagra is a species found in coastal regions of the Americas, inhabiting meso-intertidal environments, rocky shores, and exhibiting cryptic behavior. Its feeding habits are opportunistic and diversified, associated with the availability of local resources. The aim of this study is to report the first occurrence of cannibalism in E. gonagra in the natural environment. The report occurred in Northeastern Brazil ecoregion, during a nocturnal observation at low tide in April 2023. Local anthropization, the presence of endoparasites, or a density-dependent relationship of E. gonagra in relation to resource availability may have led to this uncommon behavior for the species.